2008
DOI: 10.1093/eurheartj/ehn155
|View full text |Cite
|
Sign up to set email alerts
|

Multiple source surveillance incidence and aetiology of out-of-hospital sudden cardiac death in a rural population in the West of Ireland

Abstract: The burden of SCD in the West of Ireland is considerable. The vast majority of cases occur in the home. Survival rates in this rural population cohort remain low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 37 publications
3
58
0
3
Order By: Relevance
“…In recent prospective studies using multiple sources in the United States, 6,7 Netherlands, 8 Ireland, 9 and China, 10 SCD rates range from 50 to 100…”
Section: Epidemiologymentioning
confidence: 99%
“…In recent prospective studies using multiple sources in the United States, 6,7 Netherlands, 8 Ireland, 9 and China, 10 SCD rates range from 50 to 100…”
Section: Epidemiologymentioning
confidence: 99%
“…The incidence of SCD in the United States ranges between 180,000 and 450,000 cases annually, depending on the definition used 4,5,8,9,10 . In a more specific way, prospective studies using multiple sources developed in the United States, Netherlands, Ireland, and China have shown that SCD rates ranging from 50 to 100 per 100 000 in the general population 10,11,12,13,14,15,16 . The global burden of SCD remains high despite the fact that several factors have already been described which increase the risk of SCD in the general population 9,10 .…”
Section: Sudden Cardiac Death In Epilepsy Disappoints But Epileptolomentioning
confidence: 99%
“…In the second half of the 20 th century, SCD continues to claim 250.000 to 300.000 US lives annualy [11,12]. In North America and Europe the annual incidence of SCD ranges between 50 to 100 per 100.000 in the general population [13][14][15][16]. However, even in the presence of advanced first responder systems for resuscitation of out-of-hospital cardiac arrest, the overall survival to hospital discharge was recently estimated to be only 7,9% [17].…”
Section: Sudden Cardiac Deathmentioning
confidence: 99%